2020
DOI: 10.1109/comst.2020.2988293
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Machine and Deep Learning Methods for Internet of Things (IoT) Security

Abstract: The Internet of Things (IoT) integrates billions of smart devices that can communicate with one another with minimal human intervention. It is one of the fastest developing fields in the history of computing, with an estimated 50 billion devices by the end of 2020. On the one hand, IoT technologies play a crucial role in enhancing several real-life smart applications that can improve life quality. On the other hand, the crosscutting nature of IoT systems and the multidisciplinary components involved in the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
333
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 780 publications
(414 citation statements)
references
References 269 publications
0
333
0
1
Order By: Relevance
“…Using multi-UAVs in CPS applications can extend the attack surface of the systems that can include physical and cyber vulnerabilities. Moreover the introduction of internet of things (IoT) will enhance the applications of UAV systems [216]; on the other hand, the integration into IoT systems can enlarge the vulnerability surfaces of UAVs systems, because the IoT systems have several attack surfaces [217].Therefore, with the wide range of UAV applications, security is expected to be a high priority while designing UAVs. However, [218] showed that UAVs are not as secure as expected; this study reported that man-in-themiddle attack can be launched and the UAV can be controlled even with long distances from the main controller.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Using multi-UAVs in CPS applications can extend the attack surface of the systems that can include physical and cyber vulnerabilities. Moreover the introduction of internet of things (IoT) will enhance the applications of UAV systems [216]; on the other hand, the integration into IoT systems can enlarge the vulnerability surfaces of UAVs systems, because the IoT systems have several attack surfaces [217].Therefore, with the wide range of UAV applications, security is expected to be a high priority while designing UAVs. However, [218] showed that UAVs are not as secure as expected; this study reported that man-in-themiddle attack can be launched and the UAV can be controlled even with long distances from the main controller.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…In IoT, k-means clustering was used to distinguish Sybil attackers from normal sensors through clustering the channel vectors in industrial WSNs [20]. Nevertheless, this technique has many limitations, namely the need to have roughly equal numbers in each cluster for the algorithm to properly work, as well as the non-trivial task of choosing k [21]. Now, let us move to the deep sphere, and begin our survey by Convolutional Neural Networks (CNNs).…”
Section: B Learning Applications For Iot Securitymentioning
confidence: 99%
“…GANs may have a potential application in IoT security especially in zero-daylike threats given their ability to learn diverse attack scenarios and then to generate innovative attacks beyond the existing ones. Though, up to now the training phase of GANs still unstable and a tough task [21].…”
Section: B Learning Applications For Iot Securitymentioning
confidence: 99%
“…In [9], the authors reviewed and summarized work focusing on defending cyber-physical systems. Additionally, [10] reviews machine learning and DL methods for securing Internet of Things (IoT) technology. This paper is unique because it covers a wide array of cyber-attack types, and the approaches to detect them span a spectrum of DL techniques including convolutional neural networks (CNNs), recurrent neural networks (RNNs), and generative adversarial networks (GANs).…”
Section: Introductionmentioning
confidence: 99%